The relationship between trade openness and the inflation rate in Saudi Arabia: A cointegration approach - Othman Altwijry; Muḥammad Ṭāhir (Economies, 2025)
The relationship between trade openness and economic performance has been widely debated and researched during the last several decades. However, the specific influence of trade openness from the perspective of controlling the inflation rate is rarely researched specifically for the Kingdom of Saudi Arabia (KSA). Accordingly, this research paper attempts to test the influence of trade openness on inflation, focusing on KSA. The paper utilizes historical data from 1975 to 2023 and employs the 'Autoregressive Distributed Lag (ARDL)' and 'Nonlinear Autoregressive Distributed Lag (NARDL)' cointegration techniques to assess the responsiveness of the inflation rate to increased trade openness. The results of the ARDL demonstrated the positive influence that trade openness has on inflation, which is a rejection of Romer's hypothesis. The findings of the NARDL also rejected Romer's hypothesis by demonstrating a positive relationship between the positive shocks in trade openness and the inflation rate. Similarly, our results illustrated a significant negative impact of domestic industrialization and government expenditure on inflation. Moreover, we found that the inflation rate in KSA is significantly dependent on economic performance. Finally, our findings demonstrated that the natural resource sector is unable to explain the inflationary pressure in KSA significantly.
Keywords: 330; trade openness; ARDL; government expenditures; inflation rate; Saudi Arabia